2019
DOI: 10.1007/978-3-030-19651-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Deep Support Vector Classification and Regression

Abstract: Support Vector Machines, SVM, are one of the most popular machine learning models for supervised problems and have proved to achieve great performance in a wide broad of predicting tasks. However, they can suffer from scalability issues when working with large sample sizes, a common situation in the big data era. On the other hand, Deep Neural Networks (DNNs) can handle large datasets with greater ease and in this paper we propase Deep SVM models that combine the highly non-linear feature processing of DNNs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Although some proposals attempt to overcome this obstacle, in many cases they still struggle with large datasets. The developments in [26] describe deep ANN models for both classification and regression which leverage the loss functions of support vector machines and support vector regression models, respectively. The results show that the performance is very similar to that of the traditional models, but the training time required to learn an ANN-based model is much shorter.…”
Section: Methods: Limits and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some proposals attempt to overcome this obstacle, in many cases they still struggle with large datasets. The developments in [26] describe deep ANN models for both classification and regression which leverage the loss functions of support vector machines and support vector regression models, respectively. The results show that the performance is very similar to that of the traditional models, but the training time required to learn an ANN-based model is much shorter.…”
Section: Methods: Limits and Challengesmentioning
confidence: 99%
“…An example of research to complement certain models and trying to solve some of their problems can be found in [26]. While support vector machines (SVM) are the most successful models for supervised learning problems, it is true that they suffer from scalability problems with large amounts of data.…”
Section: A New Era For Artificial Intelligencementioning
confidence: 99%